Automatizovaná interpretace laboratorního výsledku pocítacem - Průsa, R; Hrbácek, J; Masopust, J (Casopis lekaru ceskych, 1995)
The clinician-the patient-the laboratory are parts of one communication system. Computer based communication between laboratory and clinician is fast, highly reliable, and accurate. Computer assisted interpretative reports are a natural consequence of the requirements of problem solving strategies in clinical and laboratory medicine.
Keywords: interpretace statistických dat; lidé; Clinical Laboratory Techniques; Data Interpretation, Statistical; Diagnosis, Computer-Assisted; diagnóza počítačová; Humans; klinické laboratorní techniky